2004
DOI: 10.2214/ajr.183.5.1831379
|View full text |Cite
|
Sign up to set email alerts
|

Testicular Size and Vascular Resistance Before and After Hydrocelectomy

Abstract: There is an association between the development of an idiopathic hydrocele and testicular size and vascular resistance. We believe that the increase in volume and vascular resistance is due to an increase in impedance to venous and lymphatic flow.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
1
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 12 publications
4
31
1
1
Order By: Relevance
“…Until recently, the effect of idiopathic hydrocele on the testis was poorly understood as it was thought to be completely harmless to testicular health, however Mihmanli et al [18] were able to demonstrate that idiopathic hydrocele may cause testicular enlargement and increased vascular resistance in the intratesticular arteries, thereby adversely affecting testicular function. The incidence of hydrocele in the sub-fertile men our study is consistent with reports by others [3,5].…”
Section: Discussionmentioning
confidence: 99%
“…Until recently, the effect of idiopathic hydrocele on the testis was poorly understood as it was thought to be completely harmless to testicular health, however Mihmanli et al [18] were able to demonstrate that idiopathic hydrocele may cause testicular enlargement and increased vascular resistance in the intratesticular arteries, thereby adversely affecting testicular function. The incidence of hydrocele in the sub-fertile men our study is consistent with reports by others [3,5].…”
Section: Discussionmentioning
confidence: 99%
“…Nye et al, 2 in a study of testicular blood flow, showed that there is a significant difference in the pulsatility index, resistivity index and testicular size before and after hydrocoele repair. Mihmanli et al 3 published a case report documenting absence of diastolic blood flow prior to hydrocoele repair that was reversed post-procedure. Although no intrascrotal pressures were measured in the case described, the presence of pain and absence of A pressing diagnosis -a compromised testicle secondary to compartment syndrome blood flow signifies the unusual diagnosis of a compartment syndrome within the tunica vaginalis compromising the testis.…”
Section: Discussionmentioning
confidence: 99%
“…The pathophysiology of an acquired hydrocele testis is unclear, but may result from increased serous fluid secretion, lack of efferent lymphatic's of failure of lymphatics in the mesothelial lining to reabsorb fluid [14]. The hydrostatic pressure of hydrocele has been demonstrated to be greater than the pressure of the blood vessels in the scrotum, which may create stasis in venous and lymphatic flow which results in an accumulation of fluid with an increase in scrotal size [15].…”
Section: Discussionmentioning
confidence: 99%